Safety of Women in India??? With Reference to Ambai’s “Journey-17” - A. , Jayanthi; N., S. Vishnu Priya (International Journal of Psychosocial Rehabilitation, 2020)
The main aim of this paper is to study the vulnerable life of women in Indian cities, especially in the big city of Delhi. The two young women’s lives, in “Journey-17” published in the collection A Night with a Black Spider written by C.S. Lakshmi, are taken up for study. Most of Ambai’s works explore struggle, tradition, transition, women’s bodies, sexuality, identity, rape, patriarchy, transformation of feelings, and so on that affect women’s lives. This paper focusses on the in-depth conversation of two young women called Mythili and Neerja who meet in a train going to Delhi. Through the story, Ambai has clearly depicted how a woman cannot help another woman in times of need due to her dependence on her family members. Through the story of Ambai, it tries to portray different examples of sexual abuse and molestation. The story indirectly cautions women against embarking on a journey of solitude. It indirectly emphasizes education and marriage as the means of empowerment of women. The story also highlights how women are looked down on as mere objects of sex in society and how there is no guarantee for the safety of both chastity and life of a woman in a big city like Delhi. The lives of both the women are good examples of male chauvinist society. This paper discusses the vulnerability of women both in the family and in society as portrayed by Ambai and tries to emphasize the importance of liberation of women from patriarchy, sexuality, rape, violence, marriage, and the other tangles that ensnare them and their empowerment through education and jobs.